2003
DOI: 10.1302/0301-620x.85b6.13555
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of Schmorl’s nodes

Abstract: We examined the pathogenesis of Schmorl’s nodes, correlating the histological findings from 12 lumbar vertebrae with the corresponding conventional radiographs, tomographs, MR images and CT scans. The last revealed round, often multiple cystic lesions with indistinct sclerotic margins beneath the cartilaginous endplate. The appearances are similar to the typical CT changes of osteonecrosis. Histological examination of en-bloc slices through Schmorl’s nodes gave clear evidence of subchondral osteonecrosis. Bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 15 publications
(9 reference statements)
0
40
1
6
Order By: Relevance
“…Resultados recientes proponen que este debilitamiento estaría relacionado con cambios en los patrones vasculares entre el disco y el platillo vertebral (Haidar et al 2009) o con necrosis isquémicas óseas subcondrales producidas debajo del platillo vertebral (Peng et al 2003). Además, Zhang et al (2010) plantean como hipótesis un rol destacado de causas inmunológicas en el desarrollo de los NS.…”
Section: Palabras Clave: Nódulos De Schmorl Restos Humanos Arqueológunclassified
“…Resultados recientes proponen que este debilitamiento estaría relacionado con cambios en los patrones vasculares entre el disco y el platillo vertebral (Haidar et al 2009) o con necrosis isquémicas óseas subcondrales producidas debajo del platillo vertebral (Peng et al 2003). Además, Zhang et al (2010) plantean como hipótesis un rol destacado de causas inmunológicas en el desarrollo de los NS.…”
Section: Palabras Clave: Nódulos De Schmorl Restos Humanos Arqueológunclassified
“…This indicated the presence of inflammation and edema in the vertebral bone marrow which is less emphasized clinically so far [11]. These MRI findings were not present in asymptomatic individuals which suggested that Schmorl's nodes became asymptomatic when the inflammation subsided [9].…”
Section: Imaging Evaluationmentioning
confidence: 90%
“…The radiological manifestation of Schmorl's nodes is an endplate indentation with an indistinct sclerotic marginal line [9]. In the lateral projection, the vertebral bodies are rather rectangular in shape.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…Schmorl's nodes have been widely assumed to be the herniation of the nucleus pulposus through the cartilaginous endplate into the body of a vertebra, ever since Schmorl first described them in 1927 [5,29]. The hypotheses of their origin and pathogenesis include developmental factors, degenerative conditions, pathological processes such as infection, neoplasia and trauma, and bone necrosis beneath the endplate [1,5,8,14,23,26,28,30,31]. The endplate degenerative changes, also known as Modic changes, were proposed independently by de Roos et al [7] and Modic et al [18,19] according to signal intensity changes of the endplate beneath the cartilage endplate and the adjacent marrow on MRI.…”
Section: Discussionmentioning
confidence: 99%